Sosialisasi Pendekatan Berbasis Data dalam Pemberdayaan Ekonomi Umat Berbasis Masjid Melalui Bazar Syariah - Syafran Nurrahman; Aep Saefullah; M.Tafsiruddin; Tohiroh Tohiroh; Sitti Aliyah Azzahra; Abdul Kohar; Iskandar Iskandar; Anggoro Dwi Swasono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Mosque-based community economic empowerment activities have significant potential to improve community welfare, particularly for small businesses in the mosque's immediate vicinity. However, implementation is still largely conventional and lacks a data-driven approach, resulting in suboptimal beneficiary identification and activity evaluation. This community service initiative aims to promote a data-driven approach to mosque-based community economic empowerment through sharia bazaar activities. Implementation methods include initial observation, outreach and education for mosque managers and business owners, technical assistance for sharia entrepreneurship, and activity evaluation. The results demonstrate an increased public understanding of the importance of data use in determining beneficiaries, managing bazaar activities, and developing businesses based on sharia economic principles. The outcomes of this initiative include improved data management literacy, a simple data collection format for sharia bazaar activities, and recommendations for developing a mosque-based data collection system. It is hoped that this initiative will be the first step in building a sustainable, transparent, and data-driven community economic empowerment model within the mosque environment.